Research on the use of Lemna minor duckweed biomass for wastewater treatment - Strilets, Oksana; Strelnykov, Leonid (Problems of Environmental Biotechnology, 2021)
Samples of methane tank wastewater were treated with Lemna minor duckweed, which was previously grown in laboratory and natural conditions of the reservoir, in order to study the process of assimilation of basic substances and biomass accumulation by Lemna minor duckweed taking into account the variation of wastewater concentration and the influence of cultivation conditions on the accumulation of biomass.